Respon Penonton terhadapProduct Placement dalam Sinetron(Studi Kasus Sinetron Dunia Terbalik) - Muthia Hanindar (Inter Komunika, 2021)
Advertising is the main form of communication for companies to connect with consumers. The concept of product placement is an alternative for companies that require advertising on television media. By using a literature review method, several concepts that discuss product placement resolution, additions and lack of product placement strategies, types of product placement, and product placement practices in several countries. Indonesia is one of the countries that also uses product placement strategies on soap operas which are broadcast on several national television channels. By applying the concept of ideal product placement, this advertising strategy can give a positive impression on the product image and interest in buying consumers.Keywords: communication, advertising, product placement.